2009
DOI: 10.1007/s12185-009-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and prognosis of chronic myeloid leukemia treated with imatinib mesylate in a Chinese population

Abstract: There is limited data from developing countries on the current status of imatinib treatment for chronic myeloid leukemia (CML), thus we retrospectively analyzed 116 Chinese CML patients who received imatinib between 2003 and 2008. The response rates for 102 patients in chronic phase were: complete hematologic, 94.1%; complete cytogenetic, 69.6%; and complete molecular response, 54.9%. For 14 patients in the accelerated phase, the respective response rates were 85.7, 35.7 and 28.6%. The 3-year progression-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our previous study also confirmed that grade 3 or 4 leukopenia was associated with a lower rate of CCR [17]. The suboptimal drug dosage that results from frequent treatment interruptions or dose reductions is considered to be a main contributing factor.…”
Section: Discussionsupporting
confidence: 78%
“…Our previous study also confirmed that grade 3 or 4 leukopenia was associated with a lower rate of CCR [17]. The suboptimal drug dosage that results from frequent treatment interruptions or dose reductions is considered to be a main contributing factor.…”
Section: Discussionsupporting
confidence: 78%
“…Pigmentary abnormalities are seen not only in patients with CML, but also in patients with gastrointestinal stromal tumour and patients with dermatofibrosarcoma protuberans, after treatment with imatinib . Total or partial body hypopigmentation caused by imatinib has frequently been reported in Asian and black populations whereas it has been reported only occasionally in white patients, probably because it is less obvious with a lighter skin colour. In the current study, imatinib showed potent inhibition of total melanin content in cultured normal human melanocytes, which is in line with a previous report showing low melanin content in some of the skin biopsy specimens of these light‐skinned patients treated with imatinib …”
Section: Discussionmentioning
confidence: 99%
“…Generalized skin hypopigmentation is also a common side effect of imatinib, which occurs in 33–85% of patients, according to a series of clinical studies, mainly from Asia . We previously reported favourable therapeutic efficacy but a high incidence (77.6%) of generalized skin hypopigmentation during imatinib treatment in 116 Chinese patients with CML …”
Section: Introductionmentioning
confidence: 99%
“…There are several published accounts of the use of imatinib in countries with limited resources, including Brazil 110, Pakistan 111, India 112, Mexico 113, and China 114 (Table III). The number of children and adolescents is not provided in any of these accounts but the overall experience matched that in industrialized societies with respect to hematological, cytogenetic, and molecular genetic responses.…”
Section: Reported Experience In Developing Countriesmentioning
confidence: 99%